2013
DOI: 10.1128/aem.00925-13
|View full text |Cite
|
Sign up to set email alerts
|

Ca 2+ -Citrate Uptake and Metabolism in Lactobacillus casei ATCC 334

Abstract: The putative citrate metabolic pathway in Lactobacillus casei ATCC 334 consists of the transporter CitH, a proton symporter of the citrate-divalent metal ion family of transporters CitMHS, citrate lyase, and the membrane-bound oxaloacetate decarboxylase complex OAD-ABDH. Lactobacillus represents a large genus of Gram-positive bacteria that contains over 100 species (1). Among these, Lactobacillus casei is a facultative heterofermentative lactic acid bacterium (LAB) that can be isolated from diverse environmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 43 publications
1
20
0
1
Order By: Relevance
“…Lazzi et al (2014) predicted the monocistronic transcription and showed that this gene is overexpressed when L. rhamnosus grows in a cheeselike medium. Similarly, Mortera et al (2013) suggested that the growth of L. casei in a substrate lacking sugars and rich in citrate principally leads to the activation of this metabolic pathway, instead of those involving PFL or PDH.…”
Section: Resultsmentioning
confidence: 96%
“…Lazzi et al (2014) predicted the monocistronic transcription and showed that this gene is overexpressed when L. rhamnosus grows in a cheeselike medium. Similarly, Mortera et al (2013) suggested that the growth of L. casei in a substrate lacking sugars and rich in citrate principally leads to the activation of this metabolic pathway, instead of those involving PFL or PDH.…”
Section: Resultsmentioning
confidence: 96%
“…Its presence at the end of fermentation may result from the (partial) lysis of cells and its consequent release into milk, or from its secretion during precursor/product exchanges (Mortera et al . ).…”
Section: Resultsmentioning
confidence: 97%
“…Pyruvic acid is a key intermediate in the metabolism of LAB (Mayo et al 2010). Its presence at the end of fermentation may result from the (partial) lysis of cells and its consequent release into milk, or from its secretion during precursor/product exchanges (Mortera et al 2013). Table 4 shows the relative abundance of the different volatile compounds detected after growth in milk at 30°C for 48 h. In agreement with the results obtained for organic acids, the greatest acetic acid content was obtained with the Flora Danica commercial starter.…”
Section: Resultsmentioning
confidence: 99%
“…The slight decrease in citric acid in all fermentations could be ascribed to the citrate fermentation pathway via citrate lyase (Hugenholtz, 1993; Mortera, Pudlik, Magni, Alarcón, & Lolkema, 2013), resulting in the formation of acetic acid and flavor compounds (diacetyl and acetoin) as shown in Table 1 and Table 2, respectively. The star fruit juice fermented with L. helveticus (0.28 g/L) produced significantly higher level of acetic acid than that of L. paracasei (0.04 g/L) and L. rhamnosus (0.03 g/L) (Table 1), possibly due to metabolism of some amino acids such as serine and alanine.…”
Section: Resultsmentioning
confidence: 99%